Evaluation of second-line apatinib plus irinotecan as a treatment for advanced gastric adenocarcinoma or gastroesophageal conjunction adenocarcinoma: a prospective, multicenter phase II trial - Qu, Jinglei; He, Xin; Luo, Ying; Yu, Ping; Chen, Ying; Liu, Jing; Wang, Xin; Wang, Chang; Liang, Tingting; Bai, Yuxian; Han, Yu; Man, Li; et al. (Frontiers in Oncology, 2023)
Objective Apatinib and irinotecan are used as systematic therapies for advanced gastric adenocarcinoma (GAC) and gastroesophageal junction adenocarcinoma (GEJA), while the evidence for their combination as second-line therapy in these patients is limited. This study aimed to evaluate the efficacy and safety of second-line apatinib plus irinotecan for the treatment of GAC and GEJA. Methods In this prospective, multicenter phase II clinical study, 28 patients with advanced GAC or GEJA who received second-line apatinib plus irinotecan were recruited. Results In total, 1 (3.6%) patient achieved complete response, 7 (25.0%) patients achieved partial response, 13 (46.4%) patients had stable disease, and 4 (14.3%) patients showed progressive disease, while clinical response was not evaluable or not assessed in 3 (10.7%) patients. The objective response rate and disease control rate were 28.6% and 75.0%, respectively. Meanwhile, the median (95% confidence interval (CI)) progression-free survival (PFS) was 4.5 (3.9-5.1) months, and the median (95% CI) overall survival (OS) was 11.3 (7.4-15.1) months. By multivariate Cox regression analysis, male sex, liver metastasis, and peritoneal metastasis were independently associated with worse PFS or OS, while treatment duration ≥5 months was independently associated with better OS. In terms of the safety profile, 89.3% of patients experienced treatment-emergent adverse events of any grade, among which 82.1% of patients had grade 1-2 adverse events and 64.3% of patients had grade 3-4 adverse events. Conclusion Apatinib plus irinotecan as second-line therapy achieves a good treatment response and satisfactory survival with tolerable safety in patients with advanced GAC or GEJA.